Influence of manufacturing methods on the tribological properties of rapeseed oil lubricants - Padgurskas, Juozas; Rukuiža, Raimundas; Meškinis, Algirdas; Kreivaitis, Raimondas; Spruogis, Bronislovas (Transport, 2016)
Tribological properties of rapeseed oils manufactured and processed by different methods and modified by the anti-wear additives were analysed. Tribological tests presented that unrefined rapeseed oil has better wear resistance compared to refined oil. Modification of rapeseed oil with 2% of special biological anti-wear additives has the greatest influence on refined rapeseed oil. Chemical analysis shows that refinement removes acids from oil. Refinement and lower acidity allows more efficient operation of special biological anti-wear additives. First published online: 15 Jun 2015